1997
DOI: 10.1021/jp971941+
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sequential Ligation of Molybdenum Cation by Chalcogenides on Electronic Structure and Gas-Phase Reactivity

Abstract: The molybdenum chalcogenide cations MoX n + (X = O, S; n = 1−3) are studied by a combined experimental and theoretical approach. The monoligated species MoO+ and MoS+ both have (4Σ-) ground states that formally arise from spin-pairing of Mo+ (6S) with O (3P) and S (3P), respectively. Similarly, the bent triatomic MoX2 + cations exhibit doublet ground states (2A1). The trichalcogenides MoO3 + and MoS3 + also have doublet ground states and exhibit similar C 3 v -symmetrical structures; however, distinct energe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
101
1
23

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 148 publications
(143 citation statements)
references
References 66 publications
18
101
1
23
Order By: Relevance
“…H-atom abstraction from methane by MnO ϩ (51) and MgO ϩ (62) is also promoted by the radical character of the oxygen atom, although theory implies a significant participation of the metal and the formation of an insertion intermediate (62,81), as is reflected by the significant KIEs. MoO 3 ϩ exhibits a KIE of the same magnitude, thus pointing to the operation of a similar mechanism (60). In the case of OFeOH ϩ (59) and FeO ϩ (52, 53), even larger KIEs are observed that, at least in the latter case, can be ascribed to the formation of an intermediate insertion species in conjunction with spin cross-over (81)(82)(83)(84)(85).…”
Section: Ligated Metal Cationsmentioning
confidence: 70%
“…H-atom abstraction from methane by MnO ϩ (51) and MgO ϩ (62) is also promoted by the radical character of the oxygen atom, although theory implies a significant participation of the metal and the formation of an insertion intermediate (62,81), as is reflected by the significant KIEs. MoO 3 ϩ exhibits a KIE of the same magnitude, thus pointing to the operation of a similar mechanism (60). In the case of OFeOH ϩ (59) and FeO ϩ (52, 53), even larger KIEs are observed that, at least in the latter case, can be ascribed to the formation of an intermediate insertion species in conjunction with spin cross-over (81)(82)(83)(84)(85).…”
Section: Ligated Metal Cationsmentioning
confidence: 70%
“…[3] Dabei wurden massenselektierte, sich im Grundzustand befindende Metalloxide mit unterschiedlicher Stöchiometrie untersucht, unter anderem [MgO] + , [4] [FeO] + , [5] [MoO 3 ]C + , [6] [ReO 3 (OH)]C + , [7] [OsO 4 ]C + , [8] [V 4 O 10 ]C + [9] und oligomere [(Al 2 O 3 ) x ]C + -Cluster (x = 3-5). [10] Unter den Aluminiumoxidcluster-Kationen zeigten die mit einer ungeraden Zahl an Aluminiumatomen, die folglich über kein sauerstoffzentriertes Radikal verfügen, keinerlei Reaktivität gegenüber Methan.…”
unclassified
“…6 + mit einem Argonpuls thermalisiert. [18] Nach sorgfältiger Re-Isolierung und einer variablen Reaktionszeit von 0-5 s wurden die Ionen über eine Standard-Anregungs-Detektions-Sequenz charakterisiert.…”
unclassified
“…[9] Auch experimentell sind die Elementarschritte in der Chemie des Magnesiums und seiner Oxide vielfach untersucht worden, [12][13][14][15][16][17][18][19] [20] von wässrigen Magnesium(II)-nitrat-Lösungen bei härteren Ionisierungsbedingungen vor und berichten erstmals von der Gasphasenreaktivität dieses Kations. [21][22][23] + gefunden (KIE = 2.0), [29] während im [V 4 kann, der KIE nur 1.35 beträgt [30] und damit nahe dem KIE von ca. 1.3 für die H(D)-Abstraktion aus Methan durch freie OH-Radikale liegt.…”
unclassified